2010
DOI: 10.1016/j.eurpsy.2009.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Depression in middle-aged and older first generation migrants in Europe: Results from the Survey of Health, Ageing and Retirement in Europe (SHARE)

Abstract: We found a higher prevalence of depression in first-generation migrants aged 50 years or older, together with relevant geographical variation. This difference was not due to other known predictors of depression in older age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
1
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 52 publications
3
72
1
8
Order By: Relevance
“…Anxiety, depression and an increased risk for psychotic disorders have been reported to be prevalent in some migrant populations (Odegaard 1932;Coid et al 2008;Silveira et al 2002;Aichberger et al 2010;Bhugra 2004). These findings are explained, at least to some extent, in terms of higher social adversity, migrant stress, social isolation, depression, loneliness and poor living conditions of the migrant populations.…”
Section: Psychic Costs Of (Return) Migrationmentioning
confidence: 64%
“…Anxiety, depression and an increased risk for psychotic disorders have been reported to be prevalent in some migrant populations (Odegaard 1932;Coid et al 2008;Silveira et al 2002;Aichberger et al 2010;Bhugra 2004). These findings are explained, at least to some extent, in terms of higher social adversity, migrant stress, social isolation, depression, loneliness and poor living conditions of the migrant populations.…”
Section: Psychic Costs Of (Return) Migrationmentioning
confidence: 64%
“…It has been reported that immigrants are at greater risk for depression and dysphoric disorders, and that female immigrants with dysphoric disorders more often use secondary‐ and tertiary healthcare services than non‐immigrants 19, 20, 21. Thus, the inverse association with acute morbidity in certain ethnic groups could reflect a higher prevalence of psychosomatic disorders in this population.…”
Section: Discussionmentioning
confidence: 99%
“…In einigen Bereichen zeigt sich zudem, dass die gesundheitliche Lage von Menschen mit Migrationshintergrund schlechter ist als die der einheimischen Bevölkerung. So gibt es Hinweise darauf, dass Menschen mit Migrationshintergrund ihren Gesundheitszustand subjektiv schlechter bewerten und auch die psychische Gesundheit in der Bevöl-kerung ohne Migrationshintergrund besser ist [4,[9][10][11]. Zudem nehmen Menschen mit Migrationshintergrund manche Gesundheitsleistungen seltener in Anspruch [12][13][14][15].…”
unclassified